Analisis Semiotika Pada Puisi “Mata-Mata” Karya Heri Isnaini - Sabrina Yulia Isnani (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Poetry is a literary work that expresses thoughts and expresses the soul through aesthetic words. Poetry is also a literary work in which there are many signs, both in the form of meanings that need to be translated by the readers themselves and linguistic markers that do not require reinterpretation. Semiotics is a field of science that examines the role of signs in a literary work. The sign and everything related to the sign, both the way the sign is sent and received, will have meaning and significance. This study aims to determine the markers in a poem by Heri Isnaini entitled “Mata-Mata” using Charles Sanders Peirce's semiotic theory. This study used descriptive qualitative method. Research on this poem is considered interesting because the use of diction in it only has slight differences and seems repetitive. Therefore, semiotics has an important role in analyzing a poem so that the poem can provide an overview and understanding to the reader.